2016
DOI: 10.1111/dmcn.13359
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for dental caries among children with cerebral palsy in a low‐resource setting

Abstract: Early oral health preventive care is required for children with CP because dental caries is highly prevalent in these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(72 citation statements)
references
References 17 publications
6
56
1
9
Order By: Relevance
“…Studies have shown that the prevalence of caries experience was higher in individuals who cleaned their teeth less than once a day than those whose teeth were cleaned at least once a day [13]. For this reason, tooth brushing twice a day can provide an effective maintenance of the oral cavity.…”
Section: Oral Hygiene 21 Oral Hygiene and Cpmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that the prevalence of caries experience was higher in individuals who cleaned their teeth less than once a day than those whose teeth were cleaned at least once a day [13]. For this reason, tooth brushing twice a day can provide an effective maintenance of the oral cavity.…”
Section: Oral Hygiene 21 Oral Hygiene and Cpmentioning
confidence: 99%
“…This phenomenon has been evaluated by studies in Brazil, Bangladesh, and Japan. Determinations were made on the effects of oral health care access and dental caries progression in LMIC [3,13,16]. Results displayed that progression of dental caries was reduced once handicapped children participated in the funded rehabilitative programs of oral health professionals [16].…”
Section: Frequent Dental Visits and Cpmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Essa dificuldade em exercer práticas participativas e dialógicas, com os pacientes, em educação em saúde, pode ser reflexo da própria formação acadêmica dos profissionais de saúde, que geralmente é pautada em metodologias de ensino-aprendizagem centradas no professor, fazendo que se reproduza nos serviços o mesmo modelo pedagógico que eles foram formados. 16,17 Sendo assim, a maneira como os futuros profissionais adquirem os conhecimentos necessários às suas práticas clínicas e educativas revela a influência do meio acadêmico como também de aspectos sociais, políticos, culturais e econômicos. A principal fonte de informações da população acerca do tema saúde bucal e a maneira adequada de prevenção dos problemas bucais, em diferentes países, é o cirurgião-dentista, representando 57%, 90%, 82,3%, 35,9%, 78% e 39,3%, respectivamente, em pesquisas realizadas por Glasrud, Frazier (1988), 18 23 A principal fonte de orientação sobre higiene bucal, entre alunos do primeiro ano, foi de origem familiar (70%).…”
Section: Participantesunclassified